2005
DOI: 10.1111/j.1600-6143.2005.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Heme Oxygenase‐1 in Human Livers Before Transplantation Correlates with Graft Injury and Function After Transplantation

Abstract: Upregulation of heme oxygenase-1 (HO-1) has been proposed as an adaptive mechanism protecting against ischemia/reperfusion (I/R) injury. We investigated HO-1 expression in 38 human liver transplants and correlated this with I/R injury and graft function. Before transplantation, median HO-1 mRNA levels were 3.4-fold higher (range: 0.7-9.3) in donors than in normal controls. Based on the median value, livers were divided into two groups: low and high HO-1 expression. These groups had similar donor characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 51 publications
5
50
1
Order By: Relevance
“…Previous reports identified Kupffer cells as the main source of HO-1 expression in human livers [45,64] in contrast to controversial data from rat livers, where considerable expressions of HO-1 has also been found in hepatocytes [51,65] . Besides the large body of evidence demonstrating cytoprotective effects of HO-1 upregulation in transplant models in animals [37,66,67] , Geuken et al [45] suggested that high HO-1 overexpression in Kupffer cells in human liver allografts may contribute to an increased cell injury. In general, the role of Kupffer cells in fibrosis is controversial.…”
Section: How Does Ho-1 Overexpression Increase Cholestasis-induced LIcontrasting
confidence: 39%
See 2 more Smart Citations
“…Previous reports identified Kupffer cells as the main source of HO-1 expression in human livers [45,64] in contrast to controversial data from rat livers, where considerable expressions of HO-1 has also been found in hepatocytes [51,65] . Besides the large body of evidence demonstrating cytoprotective effects of HO-1 upregulation in transplant models in animals [37,66,67] , Geuken et al [45] suggested that high HO-1 overexpression in Kupffer cells in human liver allografts may contribute to an increased cell injury. In general, the role of Kupffer cells in fibrosis is controversial.…”
Section: How Does Ho-1 Overexpression Increase Cholestasis-induced LIcontrasting
confidence: 39%
“…Moreover, increased HO-1 expression was shown in human NASH patients, reflecting the severity of the disease and the progression of liver failure [44] . Furthermore, a dual role for HO-1 expression in human liver transplants, with either cytoprotection or increased cytotoxicity, depending on the initial level of overexpression could be demonstrated [45] . These results point towards the potentially different effects of HO-1, which may be neither exclusively cytoprotective nor exclusively cytotoxic.…”
Section: How Does Ho-1 Overexpression Increase Cholestasis-induced LImentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrate that exogenous CO suppresses early pro-inflammatory and stress-response gene expression and efficiently improves hepatic I/R injury by downregulation of the MEK/ERK1/2 signaling pathway with CO. CO production, evaluated by CO-Hb, is associated with improved function in liver-transplanted patients [50] . Furthermore, an increase in HO-1 during transplantation is more protective than high HO-1 expression before transplantation [51] . Buis et al [52] have shown that donor HO-1 genetic polymorphism may influence the outcome of liver transplantation.…”
Section: Heme Oxygenase Confers Protection Versus Different Types Of mentioning
confidence: 99%
“…HO-1 is also known as a heat shock protein 32 (hsp32), which is an integral membrane protein of the smooth endoplasmic reticulum (Lin, Weis et al 2007), and is the only inducible isoform of HO. The up regulation of HO-1 provides protection against cellular stress including oxidative stress, heavy metal toxicity, UV radiation, and inflammation, thus preventing deleterious effects of Heme and mediating anti-inflammatory and antiapototic functions (Geuken, Buis et al 2005;Datta, Banerjee et al 2010). HO-1 may facilitate the repair of injured tissues through inhibition of infiltrating inflammatory cells (Datta, Dormond et al 2007).…”
Section: Heme/heme Oxygenase-1 (Ho-1)mentioning
confidence: 99%